Characterization of 30 Selected Jasminum Accessions in Thailand Based on Microscopic and RAPD Fingerprinting - Jindaporn Phithaksilp (Science Faculty of Chiang Mai University, 2019)
Jasminum (family Oleaceae) have a long history usage in traditional medicine, perfumery and flavoring tea. Jasminum species possess their similar morphology and vernacular name resulting in unintentional substitution. Characterization plays an important role for herbal usage. Since microscopic characteristics as well as genetic relationship assessments of Jasminum accessions are still limited. Thirty Jasminum accessions obtained from 3 different locations in Thailand (n=90) were evaluated for their microscopic leaf measurements (stomata number, stomata index, palisade ratio, epidermal cell number, epidermal cell area, vein termination number, vein islet number and trichome number) under microscope as well as RAPD fingerprinting. Individual sample established their microscopic characteristics and several microscopic parameters can be used for characterization and identification. Combination of several microscopic characteristics and morphology could provide more accurate data for identification of 30 Jasminum accessions. When consideration their phylogenetic relationship among 30 Jasminum accessions, RAPD marker amplified the reproducible 217 bands among these, 155 bands (71.43%) were found to be polymorphic. The similarity index ranging from 0.022-0.477 indicated their genetic diversity. A dendrogram constructed according to the UPGMA cluster analysis could be divided 30 Jasminum accessions into 3 main clusters. In conclusion, microscopic characteristics and RAPD fingerprinting can be used to characterize 30 Jasminum accessions. The phylogenetic relationship was not associated with their botanical characteristics. The data obtained from this study could be helpful for accurate identification of medicinal plants for their safety and efficacy usage.